1998
DOI: 10.1007/s00585-998-1039-0
|View full text |Cite
|
Sign up to set email alerts
|

<i>Letter to the Editor:</i> Solar-cycle variation of the daily <i>fo</i>F2 and M(3000)F2

Abstract: solar or ionospheric indices. One step towards optimising that adjustment is to examine the extent to which daily values depend on daily solar activity. The present investigations therefore consider the correlation with daily sunspot number R, whereas monthly median values are known to correlate best with 12-month running mean sunspot number R 12 . Data and analysesIn particular, Student's t-test and Fisher's F-test have been applied to determine the significance of the higher-order polynomial coefficients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…We identified that for application purposes, a quadratic regression is an optimum choice, and higher‐order regressions cannot significantly improve the fitting anymore. Similar quadratic regressions have been used in the work of Gupta and Singh [2001], Huang [1967], Kouris et al [1998], Liu et al [2004a], Sethi et al [2002], and so on. The same conclusion can also be drawn from the monthly median data, although we only showed the analyses of the daily data here.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified that for application purposes, a quadratic regression is an optimum choice, and higher‐order regressions cannot significantly improve the fitting anymore. Similar quadratic regressions have been used in the work of Gupta and Singh [2001], Huang [1967], Kouris et al [1998], Liu et al [2004a], Sethi et al [2002], and so on. The same conclusion can also be drawn from the monthly median data, although we only showed the analyses of the daily data here.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the solar activity effects of electron density in the ionosphere show interesting altitudinal dependence [e.g., Su et al , 1999] and the behaviors of TEC and N m F 2 may be different in some aspects. Linear and saturation effects are found in the solar activity dependency of daytime N m F 2 or f o F 2 [e.g., Gorney , 1990; Huang , 1967; Kane , 1992; Kouris et al , 1998; Lei et al , 2005; Liu et al , 2004a, 2006; Pancheva and Mukhtarov , 1998; Richards , 2001; Rishbeth , 1993; Sethi et al , 2002; Whalen , 2004; Zhang and Holt , 2007]. The amplification effect can be detected sometimes in nighttime N m F 2 [e.g., Chen et al , 2008; Liu et al , 2004a].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, ionospheric data may be roughly classified into the groups of solar maxima and solar minima according to solar activity indices such as F 10.7 (10.7 cm solar radio flux) to investigate ionospheric diurnal variations at different solar activity levels. The relationships between N mF2 and solar activity indices are usually nonlinear (e.g., Chen et al, 2008;Chen and Liu, 2010;Kouris et al, 1998;Richards, 2001;Sethi et al, 2002). In this paper NmF2-F 10.7 quadratic fittings are used to more accurately normalize N mF2 to two solar activity levels, F 10.7 = 80 (a low solar activity level) and F 10.7 = 200 (a high solar activity level).…”
Section: Data Analysis Methodsmentioning
confidence: 99%